Linear and Nonlinear Controllers Applied to Fixed-Wing UAV. (14th January 2013) - Espinoza, Tadeo; Dzul, Alejandro; Llama, Miguel
This article presents a comparison of controllers which have been applied to a fixed-wing Unmanned Aerial Vehicle (UAV). The comparison is realized between classical linear controllers and nonlinear control laws. The concerned linear controllers are: Proportional-Derivative (PD) and Proportional-Integral-Derivative (PID), while the nonlinear controllers are: backstepping, sliding modes, nested saturation and fuzzy control. These controllers are compared and analysed for altitude, yaw and roll by using simulation tests.